New taxa in the genus Neolarnaca Gorochov, 2004 (Orthoptera: Gryllacrididae) based on specimens from Yunnan and Guangxi, China - Yang, Dongdong; Peng, Xiaoyu; Bian, Xun (Zootaxa, 2021)
This study provides descriptions of one new subspecies, Neolarnaca vera guoi ssp. nov., and the tegminal veins of Neolarnaca longipenna Bian & Shi, 2016. A key to the species of Neolarnaca is provided.